ANALISIS DAN PERANCANGAN SISTEM PENUNJANG KEPUTUSAN KELAYAKAN PENGAJUAN KREDIT MOBIL MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS : PT.BCA FINANCE CABANG JAMBI) - Rofi’i, Imam; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2018)
PT BCA FINANCE Is a car finance company that has stood since 1981. Needs car today has become a primary requirement. The number of people who want to buy a car on credit to make a lot of file submission of credit that must be in selection. The selection process manually makes it difficult to make credit worthiness decisions, so that the credit application information received by the prospective customer becomes slow. The purpose of this research is to analyze the current system in pt bca finance and to design a decision support system of credit proposal on pt bca finance. Benefits to be gained from this decision support system in order to facilitate branch heads in making decisions so that information received by prospective customers to be fast. The methodology used in this study is literature study, data collection, system analysis, decision support system design, and conclusion. The design of this decision support system using object-based modeling techniques to describe the analysis and design of the system, namely in the form of use case diagrams, class diagrams, and activity diagrams. The output of this research is the design of system prototype in accordance with the analysis and design of decision support system of credit proposal on pt. Bca finance.